Pengembangan Database Sistem Penilaian dengan Manajemen Akses Terjadwal dan Verifikasi OTP Email - Muhammad Agung; Baso Riadi Husda (Progressive Information, Security, Computer, and Embedded System, 2025)
The rapid advancement of information technology has driven academic services to require increasingly reliable and secure systems, particularly in the assessment domain, which plays a crucial role in the learning process. This study was initiated based on findings of security issues in an existing academic grading system at a higher education institution, including unauthorized changes to student grades and vulnerabilities caused by outdated frameworks. This research aims to develop a grading system database design equipped with scheduled access management and One-Time Password (OTP) email verification to enhance the security of assessment processes. The study employs a Research and Development (R&D) approach aligned with the System Development Life Cycle (SDLC) prototyping model. The results indicate that the newly designed database using PostgreSQL successfully supports access restriction based on assessment schedules, while the integration of OTP verification effectively prevents unauthorized account usage. System testing by a supervisor demonstrated that almost all key features operated with “fully successful” status. Therefore, the developed product is considered effective in resolving security issues within academic grading systems and can serve as a reference for similar system development efforts in higher education institutions.